A high-resolution remote sensing-based composite index for monitoring agricultural drought in India - Alka Rani; Vinay Kumar Sehgal; Rajkumar Dhakar; Ravinder Kaur; Rabi Narayan Sahoo; Vijay Kumar Prajapati; Christopher Neal; Michael Hayes; Mark Svoboda; Tsegaye Tadesse; Brian Wardlow; John Swigwart (Environment, Development and Sustainability, 2026)

Temperature variability in the Peruvian Andes during the past ~2700 years based on glycerol dialkyl glycerol tetraethers - Jarunetr (Nadia) Sae-Lim; Bronwen L. Konecky; Isla S. Castañeda; Jack A. Hutchings; Neal Michelutti; Christopher Grooms; Jeffrey Salacup; John P. Smol (Organic Geochemistry, 2026)

A framework for integrating spatiotemporal deep learning methods with landsat for annual land cover and impervious surface mapping - Rylie Fleckenstein; Danika Wellington; Suming Jin; Heather Tollerud; Jesslyn F. Brown; Jon Dewitz; Neal J. Pastick; Christopher P. Barber; Austin O’Brien; Mark Spanier (Remote Sensing of Environment, 2026)

Biomarker evidence for arid intervals during the past ∼1,800 years in the central Andean highlands - Jarunetr N. Sae-Lim; Bronwen L. Konecky; Jack A. Hutchings; Neal Michelutti; Christopher Grooms; Mathias Vuille; Isla S. Castañeda; John P. Smol (Earth and Planetary Science Letters, 2025)

Lake energy balance response to 21st century warming in the tropical high Andes - Jarunetr (Nadia) Sae-Lim; Bronwen L. Konecky; Carrie Morrill; Neal Michelutti; Christopher Grooms; John P. Smol (Global and Planetary Change, 2025)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Corrigendum to “Swelling of compacted bentonite in organic solvents: Correlation of rate and extent of swelling with solvent properties” [Applied Clay Science 241 (2023) 107000] - Ali Riza Erdogan; Anna C. Whitford; Thomas R. Underwood; Catriona Sellick; Radhika Patel; Neal T. Skipper; H. Christopher Greenwell (Applied Clay Science, 2023)

Swelling of compacted bentonite in organic solvents: Correlation of rate and extent of swelling with solvent properties - Ali Reza Erdogan; Anna C. Whitford; Thomas R. Underwood; Catriona Sellick; Radhika Patel; Neal T. Skipper; H. Christopher Greenwell (Applied Clay Science, 2023)

Demonstration of direct ocean carbon capture using hollow fiber membrane contactors - Joanna Rivero; Austin Lieber; Christopher Snodgrass; Zöe Neal; Marina Hildebrandt; William Gamble; Katherine Hornbostel (Chemical Engineering Journal, 2023)

Vaping THC-O Acetate: Potential for Another EVALI Epidemic - Neal L. Benowitz; Christopher Havel; Peyton Jacob; Donal F. O’Shea; Dan Wu; Jefferson Fowles (Journal of Medical Toxicology, 2023)

Modeling future asthma attributable to fine particulate matter (PM2.5) in a changing climate: a health impact assessment - Nicholas J. Nassikas; Elizabeth A. W. Chan; Christopher G. Nolte; Henry A. Roman; Niamh Micklewhite; Patrick L. Kinney; E. Jane Carter; Neal L. Fann (Air Quality, Atmosphere & Health, 2022)

Characterization of Concussive Events in Professional American Football Using Videogrammetry - Ann M. Bailey; Christopher P. Sherwood; James R. Funk; Jeff R. Crandall; Neal Carter; David Hessel; Stephen Beier; William Neale (Annals of Biomedical Engineering, 2020)

Differing limnological responses to late Holocene climate variability in the Cordillera Vilcanota, Peruvian Andes - Neal Michelutti; Pedro M. Tapia; Christopher Grooms; Andrew L. Labaj; John P. Smol (Journal of Paleolimnology, 2020)

Corticomotor function is associated with quadriceps rate of torque development in individuals with ACL surgery - Sarah A. Scheurer; David A. Sherman; Neal R. Glaviano; Christopher D. Ingersoll; Grant E. Norte (Experimental Brain Research, 2020)

Effect of γ-hydroxybutyrate (GHB) on driving as measured by a driving simulator - Evangelia Liakoni; Delia A. Dempsey; Matthew Meyers; Nancy G. Murphy; Dary Fiorentino; Christopher Havel; Christine Haller; Neal L. Benowitz (Psychopharmacology, 2018)

Selection for rapid germination and emergence may improve wheat seedling establishment in the presence of soil surface crusts - Monia Anzooman; Jack Christopher; Michael Mumford; Yash P. Dang; Neal W. Menzies; Peter M. Kopittke (Plant and Soil, 2018)

A new precipitation and drought climatology based on weather patterns - Douglas Richardson; Hayley J. Fowler; Christopher G. Kilsby; Robert Neal (International Journal of Climatology, 2018)
Weather‐pattern, or weather‐type, classifications are a valuable tool in many applications as they characterize the broad‐scale atmospheric circulation over a given region. This study analyses the aspects of regional UK precipitation and meteorological drought climatology with respect to a new set of objectively defined weather patterns. These new patterns are currently being used by the Met Office in several probabilistic forecasting applications driven by ensemble forecasting systems. Weather pattern definitions and daily occurrences are mapped to Lamb weather types (LWTs), and parallels between the two classifications are drawn. Daily precipitation distributions are associated with each weather pattern and LWT. Standardized precipitation index (SPI) and drought severity index (DSI) series are calculated for a range of aggregation periods and seasons. Monthly weather‐pattern frequency anomalies are calculated for SPI wet and dry periods and for the 5% most intense DSI‐based drought months. The new weather‐pattern definitions and daily occurrences largely agree with their respective LWTs, allowing comparison between the two classifications. There is also broad agreement between weather pattern and LWT changes in frequencies. The new data set is shown to be adequate for precipitation‐based analyses in the UK, although a smaller set of clustered weather patterns is not. Furthermore, intra‐pattern precipitation variability is lower in the new classification compared to the LWTs, which is an advantage in this context. Six of the new weather patterns are associated with drought over the entire UK, with several other patterns linked to regional drought. It is demonstrated that the new data set of weather patterns offers a new opportunity for classification‐based analyses in the UK.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Geochemistry of Tungsten and Arsenic in Aquifer Systems: A Comparative Study of Groundwaters from West Bengal, India, and Nevada, USA - T. Jade Mohajerin; Andrew W. Neal; Katherine Telfeyan; Sankar M. Sasihharan; Sophie Ford; Ningfang Yang; Darren A. Chevis; Deborah A. Grimm; Saugata Datta; Christopher D. White; Karen H. Johannesson (Water, Air, & Soil Pollution, 2014)

Erratum to: Multiscale Modeling and Data Integration in the Virtual Physiological Rat Project - Daniel A. Beard; Maxwell L. Neal; Nazanin Tabesh-Saleki; Christopher T. Thompson; James B. Bassingthwaighte; Mary Shimoyama; Brian E. Carlson (Annals of Biomedical Engineering, 2012)

Multiscale Modeling and Data Integration in the Virtual Physiological Rat Project - Daniel A. Beard; Maxwell L. Neal; Nazanin Tabesh-Saleki; Christopher T. Thompson; James B. Bassingtwaighte; Mary Shimoyama; Brian E. Carlson (Annals of Biomedical Engineering, 2012)

Investigation of changes in skeletal muscle α-actin expression in normal and pathological human and mouse hearts - O’Neal Copeland; Kristen J. Nowak; Nigel G. Laing; Gianina Ravenscroft; Andrew E. Messer; Christopher R. Bayliss; Steven B. Marston (Journal of Muscle Research and Cell Motility, 2010)

Transformation and segregation of GFP fluorescence and glyphosate resistance in horseweed (Conyza canadensis) hybrids - Matthew D. Halfhill; Laura L. Good; Chhandak Basu; Jason Burris; Christopher L. Main; Thomas C. Mueller; C. Neal Stewart (Plant Cell Reports, 2007)

Effect of acute saline volume expansion in the anaesthetised ?F508 cystic fibrosis mouse - Roger Green; William Colledge; Christopher Taylor; Jonathan Kibble; Andrew Neal (Pflügers Archiv - European Journal of Physiology, 2001)

Geological setting and SHRIMP U-Pb geochronological evidence for ca. 2680-2660 Ma lode-gold mineralization at Jundee-Nimary in the Yilgarn Craton, Western Australia - Christopher J. Yeats; Ernst A. Kohler; Neal J. McNaughton; Luke J. Tkatchyk (Mineralium Deposita, 2001)